SME SECTOR ECONOMIC POSITION IN THE EU: INSIGHTS INTO LABOUR EFFICIENCY AND PROFITABILITY - Gołaś, Zbigniew (Acta Scientiarum Polonorum. Oeconomia, 2011)
The paper presents the outcomes of the analysis of labour and profitability in micro, small and medium enterprises (SMEs) of EU countries. The analysis is based on the data provided by the EC Enterprise and Industry, covering the year 2008. According to the outcomes of regression analysis, the most important factors influencing SME profitability include: the productivity of expenses, the level of labour involvement in production, the share of added valuein incomes and labour costs. The most important factors influencing labour efficiency in the SME sector include: labour equipment and the shares of added value and production in incomes.